2015
DOI: 10.1188/15.onf.337-344
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Illness and Parental Demands: 
Coping With Cancer While Raising Minor Children

Abstract: Support for parenting needs is a key component of comprehensive cancer care. Oncology nurses should stay informed of all hospital, clinic, and community resources to facilitate access for parents. Unmet support needs indicate that improvements need to be made in access to medical appointments around family schedules, expanded resources for children, and reduction of wait times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 29 publications
0
22
0
1
Order By: Relevance
“…Although various studies have concluded that it is essential that support systems for parents with cancer include childcare services [21][22][23] , a thorough literature review failed to uncover a description of any services similar to nan for cancer patients. A meta-analysis completed in 2016 that analyzed various psychosocial interventions and support systems for parents with cancer and their families reported interventions focused on increasing family communication, enhancing child adjustment, improving mood, and reassuring parenting skills, with no evaluation of the services and no description of any childcare services 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Although various studies have concluded that it is essential that support systems for parents with cancer include childcare services [21][22][23] , a thorough literature review failed to uncover a description of any services similar to nan for cancer patients. A meta-analysis completed in 2016 that analyzed various psychosocial interventions and support systems for parents with cancer and their families reported interventions focused on increasing family communication, enhancing child adjustment, improving mood, and reassuring parenting skills, with no evaluation of the services and no description of any childcare services 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, parents with advanced and metastatic cancer perceived themselves primarily as parents and secondarily as individuals with cancer 4. As functional status declined, more distress took place in terms of participants’ perceived reduced adequacy in coping with parental demands 5.…”
Section: Commentarymentioning
confidence: 99%
“…Whereas participants actively continued to develop strategies to optimise parental roles and responsibilities such as mobilising their social network to address gaps in parenting, studies such as this and others show that parents would like more parenting-specific cancer support 4. Healthcare professionals are in a strategic position to mobilise these sources of support, such as relying more on volunteer associations and community peer groups.…”
Section: Commentarymentioning
confidence: 99%
“…Thi is the reason why patients trust nurses to hear their concerns, and help them work through the many conflictin emotions and uncertainties in advanced illness [7]. An experienced nurse avoids a one-size-fits-al approach, but rather continues assessing the individual patient's condition throughout the illness trajectory [8].…”
Section: Ethical and Moral Considerationsmentioning
confidence: 99%